(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The study was conducted to investigate the stomach content and index of food significance of Parachanna obscura, in Kiri reservoir, Shelleng, Adamawa state, Nigeria for a period of six months from May to October, 2015. A total 62 fish were collected on the landing site, caught by gill nets of various stretched mesh sizes. In which 46 (74.19 %) had contents with various degree of fullness, while 16 (25.81 %) specimens had empty stomachs. The stomach contents were analyzed using frequency of occurrence, Relative Frequency and the Point’s method. The food items in the stomach covered a wide variety, ranging from various types of Algae to insect parts. The major food items in terms of frequency of occurrence were pithopora and spirogyra had 60.87 % and 55.52 % respectively, which made them the most frequent in occurrence, insect parts appeared the least, with a 10.87 % frequency of occurrence. The Relative Frequency showed that volvox had the highest with 13.07 % while insect parts had the lowest with 0.82 %. The Index Food Significance (IFS) of P. obscura shows that Filamentous Algae and Colonial Algae are the secondary diet of the species, spirogyra (IFS=1.42 %), Pithopora (IFS=1.51 %), Ulothrix (IFS=1.10 %), Volvox (IFS=1.56 %), while its incidental diet include Green Algae, Cyanobacteria and Diatom, with IFS of <0.1. This report could help in measure towards the data needed to create a food web in Kiri reservoir, and eventually a trophic model that can be used in fisheries management